Testing the Impact of FFC‐AL‐EIT on Psychosocial and Behavioral Outcomes in Assisted Living. Issue 2 (23rd October 2020) - Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Fix, Steven; Holmes, Sarah; Zhu, Shijun; Barr, Erik
Abstract : BACKGROUND: This study tested the impact of Function Focused Care for Assisted Living Using the Evidence Integration Triangle (FFC‐AL‐EIT) on: (1) care interactions between residents and direct care staff; and (2) behavior and psychological symptoms associated with dementia among residents. DESIGN: This was a randomized controlled trial. SETTING: A total of 59 assisted living facilities in Maryland, Pennsylvania, and Massachusetts participated. PARTICIPANTS: The sample included 550 mostly White (98%), female (69%) residents with a mean age of 89.30 (standard deviation = 7.63) years. INTERVENTION: The four‐step FFC‐AL‐EIT intervention was implemented by a function focused care nurse facilitator working with a facility champion over 12 months. The steps included: (1) environment and policy assessments; (2) education; (3) establishing resident function focused care service plans; and (4) mentoring and motivating. MEASURES: Resident descriptive data (e.g., age, sex, education, and comorbidities), depression, agitation, resistiveness to care, and the quality of care interactions were obtained at baseline and 4 and 12 months. Treatment fidelity data included environment and policy assessments, performance of function focused care by staff, and service plan assessments. RESULTS: There was a significant positive treatment effect related to depression, agitation, resistiveness to care, and quality of care interactions with either less decline or some improvement in these behaviors and symptoms in the treatment versus control group. CONCLUSION: The study provides some statistical support, which may not necessarily be clinically significant evidence, for psychosocial outcomes of residents and care interactions between staff and residents in assisted living settings.